Planktic Foraminiferal and Pteropod Contributions to Carbon Dynamics in the Arctic Ocean (North Svalbard Margin) - Anglada-Ortiz, Griselda; Zamelczyk, Katarzyna; Meilland, Julie; Ziveri, Patrizia; Chierici, Melissa; Fransson, Agneta; Rasmussen, Tine L. (Frontiers in Marine Science, 2021)
Planktic foraminifera and shelled pteropods are some of the major producers of calcium carbonate (CaCO3) in the ocean. Their calcitic (foraminifera) and aragonitic (pteropods) shells are particularly sensitive to changes in the carbonate chemistry of the ocean. These ubiquitous calcifiers thus play an important role in the inorganic and organic carbon pump. We have studied the abundance distribution (individuals m-3) of planktic foraminifera and pteropods and their contribution to inorganic carbon standing stocks (µg m-3) and production (mg m-2 day-1) along a longitudinal transect north of Svalbard at 81° N, 22–32° E, in the Arctic Ocean. This transect, sampled in September 2018, consist of seven stations covering different oceanographic regimes, from the shelf to the slope and into the deep Nansen Basin. The sea surface temperature along the transect ranged between 1 and 5 °C with CaCO3 supersaturated conditions recorded in the upper 300 m (Ω >1 for both calcite and aragonite). The abundance of planktic foraminifera ranged from 2.3 to 52.6 ind m-3 and for the pteropods from 0.1 to 21.3 ind m-3. The planktic foraminiferal population was composed mainly of the polar species Neogloboquadrina pachyderma (55.9%) and the subpolar Turborotalita quinqueloba (21.7%), Neogloboquadrina incompta (13.5%) and Globigerina bulloides (5.2%). The pteropod population was dominated by the polar species Limacina helicina (99.6%). The rather high abundance of subpolar foraminiferal species is attributed to an increased inflow of warmer Atlantic waters, known as “Atlantification”. In addition, the distribution of the marine pelagic calcifiers in the water column showed a clear pattern with shelled pteropods dominating at the surface and subsurface. Below 100 m water depth, small (90–100 µm) and average-sized foraminifera (100–250 µm) predominated. The standing stocks and production of foraminifera ranged from 10.6 to 33.1 µg CaCO3 m-3, and from 2.3 to 7.9 mg CaCO3 m-2 day-1, respectively. In contrast, pteropods ranged from 57.3 to 439.2 µg CaCO3 m-3, and from 6.1 to 227.6 mg CaCO3 m-2 day-1, respectively. The overall predominance of pteropods in this region suggest that inorganic standing stocks and production of biogenic carbonate would be reduced under the effects of ocean acidification.